Impact of budgeting process on service delivery in local authorities in Zimbabwe: a case of Harare City - Mapasure, Tafadzwa Raymond (Midlands State University, 2020)
The research aimed at assessing the impact of budgeting process on service delivery in local authorities in Zimbabwe. Special attention was on City Council as a case study for the research, targeting year 2015 and 2016. The research objectives were centered on reviewing the budget process, assess the impact of result based budgeting on service delivery, identifying the challenges in the budget process and establish if poor service delivery can be traced to poor budgeting. The research used available literature both published and unpublished to give an insight of the budgeting process. Data was gathered by way of questionnaires and interview from 27 people who were considered for the sample, out of the 27 people issued with questionnaires only 23 managed to answer and return the questionnaires. Finding were presented and analyzed and a conclusion was reached that Harare council need to improve in budget formulation as it is now an annual ritual performed to comply with statutory requirements, flexibility was an issue, transparency and accountability and address the issue of adverse variance before they become acute. The research recommended that the Harare council should address its internal control system in budget areas as resource are not being accounted for properly.